Pemberdayaan Remaja Dalam Upaya Menumbuhkan Kesadaran Masyarakat Dalam Pengelolaan Sampah - Munawir Munawir; Masnida Masnida; Mahbub Mahbub (IAI Darussalam, 2019)
Padang people in particular Andongsari is located in corner , make residents around confusion the place disposal . Cleanliness in Padang Village is very apprehensive. this because not it is the place disposal end , finally rubbish thrown away in around rivers , ravines , ditches , streams rice fields , and places others . Too the community around who doesn't too care with environment them . this have an impact not healthy on residents around . Very unfortunate , if Hamlet Andongsari to be automatic slum areas to be nest disease too. By because that , for build a sense of caring the community Hamlet Andongsari against cleanliness , us try for wake up they with hold Socialization Cleanliness . As well as giving motivation to teenagers hamlet for always share in advance hamlet beloved. We do thing that together residents with hope for cleanliness in Hamlet Andongsari can overcome , teenagers increasingly active in his organization . And realize hamlet whose citizens be aware will cleanliness that makes they always throw away garbage on the place